SND1 regulates the androgen signaling axis by stabilizing EIF3B mRNA to facilitate the deterioration of prostate cancer - Ying Li; Chengru Yang; Guoli Cui; Shiliang Gui; Linlin Jia; Yu Chen; Honglin Niu; Hua Xin (Molecular Genetics and Genomics, 2026)

Eastward radiation of C4 crops from the Hongshan culture core region initiated around 6 ka - Licheng Guo; Qiaowen Zhang; Shiling Yang; Shangfa Xiong; Zihua Tang; Zhe Liu; Jingyi Cui; Linlin Cui (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Assessing present-day tectonic stability, sea-level change, and tsunami hazards from a coastal multi-hazard GNSS station in the southern South China Sea - Qiang Qiu; Linlin Li; Mai Ye; Hongqiang Yang; Xingyu Song; Jian Ping Yin; Tingting Zheng; Jinghe Cao; Peitao Wang; Zhanying Chen; Zhiwen Zhang; Kuilin Xiao; et al. (Engineering Geology, 2026)

Comparative precipitation forecasting in the Northeastern Tibetan Plateau: Tree-ring reconstruction and future projections using machine learning and CMIP6 models - Longyun Ma; Haoyuan Xu; Jinjian Li; Zeyu Zheng; Linlin Cui; Caihong Liu; Shanlei Sun (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Network toxicology and multi-omics reveal the mechanism of testicular toxicity induced by chronic AFB1 exposure in male quails - Zhenlei Ping; Yu Wang; Linlin Fu; Xiaoying Cui; Songtao Zheng; Xiaowen Jiang; Wenhui Yu (Journal of Hazardous Materials, 2026)

Spatial heterogeneity of ice phenology in large lakes of Xinjiang, China - Kangzheng Zhong; Jiaxin Hao; Puzhe Huo; Chunpeng Chen; Linlin Cui; Liping Xu; Zhijun Li; Jiang Li; Guanghui Wei (Regional Environmental Change, 2026)

Hydrothermal response to changes in snow and vegetation cover in Xinjiang, China - Huimin Yang; Yuehong Ran; Yichi Xu; Lihong Wang; Linlin Cui; Xiangqian Li; Mengwen Peng (Journal of Environmental Management, 2026)

Transforming waste derived phosphate sources into resources for fluoride immobilization by microbially induced phosphate precipitation - Linlin Cui; Jianxing Sun; Min Huang; Guanzhou Qiu; Zhu Chen; Hongbo Zhao; Li Shen (Bioresource Technology, 2026)

Understanding eco-hydrological processes in winter wheat croplands through physically consistent modelling - Linlin Li; Yunfei Wang; Aofan Cui; Xinyu Mao; Wenjun Zhao; Wei Li (Theoretical and Applied Climatology, 2026)

Dimethyl fumarate ameliorates quinolinic acid-induced ageing and neurodegeneration in Caenorhabditis elegans - Yi Sun; Ke Zhou; Jiaorong Cui; Haoxuan Ding; Iqra Shareef; Liuliang Du; Zhen Shi; Linlin Fu; Fenfen Sun; Zuobin Zhu; Wei Pan (Biogerontology, 2026)

Extreme warming and pulsed volcanism during the Paleocene-Eocene Thermal Maximum - Abdelhamid M. Salman; Xue-Ting Wang; Zuoling Chen; Linlin Cui; Hongwei Li; Xu Wang (Science China Earth Sciences, 2026)

Sustained Swimming Training Enhances Growth and Swimming Performance in Juvenile Coho Salmon (Oncorhynchus kisutch) with Limited Effects on Osmoregulatory-Related Traits - Wenda Cui; Hexiang Yang; Shuang Song; Linlin Dai; Hongyang Chen; Junjie Bai; Binbin Xing; Xintong Qiu (Fishes, 2026)
To evaluate the effects of swimming training on growth, swimming performance, and osmoregulatory-related indices in juvenile coho salmon, freshwater-reared fish were subjected to current of 1 body length per second (BL·s−1) from December 2024 to April 2025. Fork length, body weight, condition factor, insulin-like growth factor-1 (IGF-1), and gill and intestinal Na+/K+-ATPase (NKA) protein abundance were measured monthly, and critical swimming speed (Ucrit) was evaluated after one month of training. Trained fish showed greater fork length in March and higher body weight in March and April than controls. The condition factor was higher in trained fish in February and March, but declined during spring smolt development. Swimming capacity was enhanced by training, as indicated by significantly higher Ucrit. Mean IGF-1 levels did not differ between groups, but IGF-1 correlated positively with body size only in trained fish. No significant training effect was detected for either gill or intestinal NKA protein abundance, although gill NKA increased significantly in April, likely reflecting seasonal smoltification. In addition, IGF-1 was significantly correlated with gill NKA in trained fish in March. Collectively, these results indicate that sustained swimming training improves growth and swimming performance and may enhance associations among measured physiological variables during smoltification in juvenile coho salmon.

Impact of environmental factors on the distribution characteristics of phytoplankton functional groups in Beijing - Linlin Qin; Xu Han; Ting Zhu; Yixuan Zhang; Na Cui; Yuepeng Liu; Wenyan Liang (Protist, 2026)

Effects and mechanisms of a novel multi-target regulator on serum uric acid reduction and renal injury improvement in rats with hyperuricemia and renal damage - Zhihua Xing; Yue Xu; Wen Jiang; Zhiyuan Xu; Guanghuan Shen; Na Ling; Mingyu Gao; Weina Han; Yingjie Liu; Linlin Cui (PharmaNutrition, 2026)

Synthesis of lead-free perovskite Z-scheme heterojunction CeO2/Cs3Bi2Br9 via in-situ growth strategy to promote photocatalytic CO2 reduction - Xiaodong Zhang; Xinyue Peng; Han Cui; Mai Zhang; Linlin Zhang (Journal of Environmental Chemical Engineering, 2026)

Nitrogen cycle suppression and enhanced carbon burial during the Paleocene-Eocene thermal maximum, recorded from Tarfa section, Egypt (Tethys Ocean) - Abdelhamid M. Salman; Xueting Wang; Zuoling Chen; Hongwei Li; Linlin Cui; Nageh A. Obaidalla; Xu Wang (Global and Planetary Change, 2026)

Responses of sedimentary magnetic susceptibility and metal contents to climate and anthropogenic activity changes: examination on lake records across the Asian monsoon region - Haiyang Yu; Shuangchi Liu; Jule Xiao; Xu Wang; Linlin Cui; Licheng Guo; Xueting Wang; Shihao Zhang (CATENA, 2026)

ABEEM/MM Magnesium Force Field for Proteins and Aqueous Solutions - Jing Zhang; Linan Lu; Runqiang Yu; Linlin Liu; Lei Wang; Cui Liu; Lidong Gong; Zhongzhi Yang (Interdisciplinary Sciences: Computational Life Sciences, 2026)

When did the Ancient Fen River Dry up? Timing and Mechanisms of River Abandonment in the Yuncheng Basin (Southern North China Craton) Based on Sedimentary and Paleoclimatic Evidence - Zhenhong Li; Xiaopeng Dong; Lijie Wei; Mingxing Shi; Debin Nan; Linlin Kou; Jiawei Cui; Ting Huang (Journal of Earth Science, 2026)

Cohort Profile: The Chinese Ovarian Aging Cohort (COACH) - Changjing Wang; Tingting Meng; Wei Luo; Jiangtao Zhang; Yongzhi Cao; Cheng Li; Jing Zhang; Xuan Gao; Peihao Liu; Chenxi Li; Dongshan Zhu; Tao Zhang; et al. (Phenomics, 2026)

DMSO intercalation tunes antibiofouling properties of MXene/PVDF composite membranes: Toward sustainable wastewater treatment - Chenhong Cheng; Yuanyuan Zhang; Haochuan Yang; Jie Zhang; Linlin Yang; Rubing Dong; Jiayi Cui; Yongli Qin; Xueye Wang; Xingran Zhang; Jinxing Ma; Junjian Zheng (Journal of Environmental Chemical Engineering, 2026)

Seasonal-spatial distribution and prevailing wind analysis of Martian dust devils in Amazonis Planitia using a multi-scale attention network - Linlin Shi; Gan Liu; Jialong Lai; Xu Ma; Feifei Cui; Xiaoping Zhang; Yi Xu; Qiquan Yang (Science China Earth Sciences, 2026)

An overview of GNSS for tsunami early warning: From lithosphere to ionosphere - Kejie Chen; Haishan Chai; Jiafeng Li; Guoguang Wei; Mingzhe Lyu; Wenfeng Cui; Chuang Shi; Linlin Li; Peitao Wang; Wei Lu; Jian Lin (Science China Earth Sciences, 2026)

Mechanism of liver fibrosis induced by life-long triclosan exposure in offspring rats: an adverse outcome pathway framework validated by in vivo and in vitro experiments - Fu Liu; Jianing Shang; Linlin Zheng; Xiaoyu Zhang; Anqi Cui; Xue Dou; Yunwei Li; Jieyu Liu (Archives of Toxicology, 2026)

Globally synchronous acceleration of soil formation approximately 12,000 years ago - Licheng Guo; Qiaowen Zhang; Haozhong Xue; Shangfa Xiong; Shiling Yang; Zihua Tang; Linlin Cui; Jingyi Cui; Yongda Wang; Shihao Zhang (Global and Planetary Change, 2026)

Mechanism of physicochemical changes in potato starch gel induced by citric acid-autoclaving for texture improvement and resistant starch formation - Linlin Cui; Xinzhu Wang; Shuhan Ge; Xia Li; Yu Wang; Bo Nan; Zhicheng Zhang; Yuhua Wang (Food Chemistry, 2026)

Meso–Neoproterozoic rift system along the southwestern North China Craton: evidence from recent drilling and seismic data - Zhenhong Li; Xiaopeng Dong; Haifeng Bai; Yijun Zhou; Jiawei Cui; Linlin Kou; Fang Wu (International Geology Review, 2026)

Dynamic Mechanisms of Land Use Conflict Under Main Function Oriented Zone Planning: A Case Study of Beijing-Tianjin-Hebei Region - Yang Zheng; Linlin Cheng; Junqi Wang; Yifang Wang; Huizhen Cui (Chinese Geographical Science, 2026)

Inactivation of Penicillium ochrochloron spores by pulsed light: Mechanism and preservation efficacy in strawberries - Xiaozhen Cui; Anthony Pius Bassey; Fan Wang; Shudong Xie; Dongnan Li; Linlin Fan; Yongsheng Zhu; Li Bin; Xiaoli Liu (Food Control, 2026)

Filamentous cyanobacterium Spirulina platensis mediates phosphate biomineralization for efficient fluoride immobilization and drives metabolic shift toward stress resistance and biomineralization - Linlin Cui; Zhilian Liu; Jun Suo; Yun Liu; Guanzhou Qiu; Zhu Chen; Hongbo Zhao; Li Shen (Journal of Hazardous Materials, 2025)

Covalent organic frameworks with synergistic linkages and functional groups boost electrochemiluminescence for sensitive detection of long non-coding RNA - Linlin Song; Lin Cui; Xiaoran Zou; Xueting Cao; Wenqi Chu; Wenjie Gao; Lin Cheng; Bing Sun; Chun-yang Zhang (Chemical Engineering Journal, 2025)

Nonlinear trajectory tracking control of UVMS with compositing fuzzy disturbance observer and robust state-dependent Riccati equation - Qirong Tang; Yuanjie Di; Tong Li; Yuanzhe Cui; Zongwu Xie; Linlin Feng; Min Yu (Ocean Engineering, 2025)

DHA sustains frozen-cell-induced efferocytosis by mitigating endoplasmic reticulum stress to promote inflammation resolution and bone repair - Boya Zhang; Hanze Du; Lei Huang; Lijun Liu; Jing Cui; Linlin Wen; Junguang Liu; Wenhao Zhai; Rongrong Ye; Yuhuan Li; Kexuan Liu; Wangni Xie; et al. (Chemical Engineering Journal, 2025)

Experimental investigation on local scour around a cubic artificial reef in bidirectional tidal currents - Linlin Wang; Mingda Yang; Muk Chen Ong; Fenfang Zhao; Yujie Cui; Yanli Tang (Ocean Engineering, 2025)

Tetraether-based temperature record from Lake Xingyun in southwestern China since late MIS3 and implication for regional differences in temperature reconstruction - Haiyang Yu; Xu Wang; Ming Ji; Shihao Zhang; Gaochao Pan; Licheng Guo; Linlin Cui; Xueyun Ma; Wubiao Li; Dongsheng Li (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Simultaneous fluoride, calcium, and phosphorus removal by bacterial phosphate mineralization: Reaction pathways, mechanisms, and process optimization - Linlin Cui; Zhilian Liu; Jun Suo; Jue Kang; Yun Liu; Guanzhou Qiu; Hongbo Zhao; Li Shen (Journal of Environmental Chemical Engineering, 2025)

Sponge-like PNIPAM/Fe3O4/PPy composite hydrogel actuator with rapid response, self-sensing and multiple manipulating manners for complex application scenarios - Xingchen Cui; Bing Zhang; Pingzhi Shao; Linlin Li; Shunsheng Ye; Fuqiang Fan; Yu Fu; Fanbao Meng; Tieqiang Wang (Chemical Engineering Journal, 2025)

Advances in preclinical studies of ginsenoside Rh2 in antitumor therapy - Zheng Xu; Guanghuan Shen; Zhihua Xing; Jianghan Luo; Yu Zhu; Xuan Liu; ShiHao Li; Hao Wang; Linlin Cui (Medicinal Chemistry Research, 2025)

Assessing Intra-Annual Spatial Distribution of Amphioctopus fangsiao in the East China Sea and Southern Yellow Sea Using Ensemble Models - Yan Cui; Xiaodi Gao; Shaobo Yang; Shengfa Li; Linlin Yang (Journal of Marine Science and Engineering, 2025)
Understanding the distribution pattern and its drivers of species is crucial for developing effective and sustainable management strategies. Amphioctopus fangsiao is the octopus of significant commercial and ecological value along the coast of China, with multiple distinct populations. However, research on their ecological dynamics remains limited and requires further investigation. Here, ensemble models were constructed to examine the spatio-temporal distribution and inter-populational differentiation in environmental adaptability of A. fangsiao in the East China Sea (ECS) and the South Yellow Sea (SYS). Specifically, we generated the ensemble models by integrating Gradient Boosting Machine (GBM), Generalized Linear Models (GLMs), and Maximum Entropy Models (MaxEnt) for the different populations across four seasons, using fishery-independent data collected from 2015 to 2021. The results revealed two hotspots of A. fangsiao in the ECS and SYS: one is the area of SYS along the coastal waters, with latitudes 33° N–34° N and longitudes 120° E–122° E (northern population, NP); the other one is near the Kuroshio-adjacent area with latitudes 28.5° N–29° N and longitudes 123° E–124.5° E (southern population, SP). Both NP and SP exhibited distinct seasonal habitat preferences, with key environmental drivers showing seasonal variations. The NP tended to inhabit coastal waters with lower sea surface heights (SSHs), shallower water depth, and a narrower sea bottom salinity range (SBS). In contrast, SP preferred marine environments with a thicker mixed layer thickness (MLT) and higher concentrations of bottom chlorophyll-a (Chl_b). The environmental characterization of suitable habitats revealed distinct patterns in resource utilization and environmental adaptation strategies between the two populations. This study provides fundamental data for understanding A. fangsiao population dynamics and underscores the importance of considering population-specific habitat preferences within dynamic marine environments.

Characterization of TGFβ Signaling Components in Large Yellow Croaker (Larimichthys crocea) and Their Role in Growth and Body Shape Regulation - Xuyang Jiang; Lu Zhang; Xin Hu; Mingchao Cui; Jie Li; Huang Liu; Linlin Yao (Journal of Marine Science and Engineering, 2025)
The transforming growth factor β (TGFβ) signaling axis plays a pivotal role in orchestrating a wide array of biological functions, encompassing cellular growth, proliferation, and differentiation. The aim of the present study was to identify the members of TGFβ signaling pathway and their expression patterns in large yellow croaker (Larimichthys crocea) under different culture modes. TGFβ signaling pathway and their expression patterns in fish reared under two different culture modes: Group N (2400 fish in a 120 m3 cage) and Group V (168,000 fish in a 5600 m3 aquaculture vessel). After 120 days, we analyzed 15 fish from each group and found that Group V exhibited faster growth and a slender body shape compared to Group N. Bioinformatics analysis identified 48 TGFβ superfamily members in L. crocea, including 21 ligands, 10 receptors, and 3 Smads. mRNA expression levels indicated that these signaling molecules influence growth rate and body shape through five distinct ligand–receptor–R-Smad pathways, with the INHBB-, Nodal-, and GDF3-ACVR2A-ALK4-Smad2 axis playing a predominant role in regulating these traits.

The regulation of gut microbiota and urate lowering: A study on the mechanisms of action of probiotics and plant components - Zhihua Xing; Yue Xu; Wen Jiang; Mingyu Gao; Guanghuan Shen; Yingjie Liu; Na Ling; Linlin Cui (PharmaNutrition, 2025)

Development of a data-driven automatic unstructured mesh generation tool suitable for compound flooding studies - Jaime R. Calzada; Y. Joseph Zhang; Fei Ye; Linlin Cui (Environmental Modelling & Software, 2025)

circ_0000554 promotes macrophage M2 polarization mediated by glycolytic reprogramming and aggravates COPD injury - Yamei Song; SiQin Han; Linlin Liu; Lifeng Zheng; Jing Wang; Zhaobo Cui; Xixin Yan (Toxicology Letters, 2025)

Cobalt-doped covalent organic framework effectively enhances Fenton-like activity: radical and non-radical dual pathways enhancement - Yunchao Ma; Chuanxue You; Yuxin Yao; Shengnan Qi; Tianyu Zhou; Wei Jiang; Keyu Cui; Bo Hu; Linlin Liu (Chemical Engineering Journal, 2025)

An automated river shoreline space type identification method using remote sensing data that considers space-channel attention multi-scale features - Shijiao Qiao; Wanlai Xue; Kun Jia; Jie Li; Mu Xia; Zhulin Chen; Haiying Jiang; Bo Yuan; Guofeng Tao; Yuran Cui; Linlin Zhao; Zihang Jiang; et al. (International Journal of Remote Sensing, 2025)

MVPCR: Multiplex Visual Detection Strategy Based on Ultrafast PCR for Point-of-Care Pathogens Detection Within 10 Min - Ziqin Zhang; Cui Wu; Linlin Bai; Kaiming Guo; Ting Wang; Dianwei Liu; Mingrui Zhu; Feng Qian; Fang Zhang; Rui Wang (Phenomics, 2025)

Inactivation activity and mechanism of natural antimicrobial agents against Alicyclobacillus spp. in apple juice - Rui Cai; Linlin Gao; Yuxiang Zhang; Lu Cui; Yahong Yuan; Zhouli Wang; Tianli Yue (Food Control, 2025)

Computational fluid dynamics and machine learning assisted Al-LDH adsorbent reactor design for lithium recovery from salt lakes - Jiangtao Yu; Minmeng Tang; Peng Cui; Jianquan Deng; Haiying Mi; Li Zhang; Linlin Chen; Peiwen Wu; Yanhong Chao; Wenshuai Zhu; Zhichang Liu (Desalination, 2025)

Seasonal and spatial distribution of AmphiOctopus fangsiao and Octopus variabilis in the southern Yellow and East China Seas: Fisheries management implications based on climate scenario predictions - Linlin Yang; Min Xu; Zunlei Liu; Yi Zhang; Yan Cui; Shengfa Li (Regional Studies in Marine Science, 2025)

Magnetic resonance spectroscopy for discriminating primary angiitis of the central nervous system from gliomas and lymphomas - Ping Lu; Lingyun Cui; Lulin Zhang; Huabing wang; Linlin yin; Decai Tian; Xinghu Zhang (Acta Neurologica Belgica, 2025)

Seasonal spatial distribution patterns of AmphiOctopus ovulum in the East China Sea: current status future projections under various climate change scenarios - Linlin Yang; Min Xu; Yan Cui; Shuhao Liu (Frontiers in Marine Science, 2025)
Currently, there is also little up to date information on the the current population status and life history traits of AmphiOctopus ovulum , a very often seen cephalopod species in the East China Sea. It is therefore important to figure out the seasonal spatial distribution of this species, both in terms of number and biomass, and the environmental variables which determine them. Additionally, climate change plays an important role in determining the characteristics of individual species and thus on the ecosystems they inhabit. We set out to understand the responses of A. ovulum to habitat variables and to make projections based on the climate change scenarios described in the IPCC’s SSP1-2.6 and SSP5-8.5 criteria. We carried out seasonal bottom trawling surveys in the East China Sea region during 2018 and 2019 to fill this knowledge gap. Our results showed that the average individual size values ranged from 17.80−43.00 g·ind -1 in spring and 23.49−33.00 g·ind -1 in summer; the measured sea bottom temperature, sea bottom salinity, and depth value ranges were 10.81−27.06°C, 31.73–35.25‰, and 91–103 m independently in spring to winter. Our study showed that A. ovulum was distributed in the area between 27°–29°N, 122.5°–125°E during spring to autumn, and expanded into the area between 26.5°–32.5°N, 121°–124.5°E in winter. The core habitat of A. ovulum was centered on the area between 27.5°–28°N, 122.5°–123.5°E, and can be expected to expand to the northeast and southwest independently under the most likely global warming scenarios. Our results will benefit the development of suitable conservation measures for cephalopod habitats, and incorporate the impacts of climate change into fisheries management programs.

Fabrication and characterization of gelatin/carboxymethyl chitosan composite film incorporated with carvacrol and its preservation efficacy in Chinese mitten crab (Eriocheir sinensis) - Anthony Pius Bassey; Xiaozhen Cui; Isaiah Henry Ibeogu; Fan Wang; Mustapha Muhammad Nasiru; Hadiza Kabir Bako; Linlin Fan; Xiaoli Liu (Food Hydrocolloids, 2025)

Spatiotemporal evolution of wildfire activity during the Paleocene-Eocene Thermal Maximum in China - Xue-Ting Wang; Zuoling Chen; Linlin Cui; Xu Wang (Science China Earth Sciences, 2025)

A 219-year tree-ring evidence revealing the influence of the Atlantic Multi-decadal oscillation on annual mean temperature in the northern Western Sichuan Plateau - Xu Wu; Jinjian Li; Linlin Cui; Xiaofei Wu; Kaiqing Yang; Alma Lorelei de Jesus (Climate Dynamics, 2025)

Indian summer monsoon variations since late MIS3: A perspective from multiproxy evidence from Lake Xingyun in southwestern China - Haiyang Yu; Linlin Cui; Xu Wang; Xueyun Ma; Bing Xu; Wubiao Li; Xueting Wang (Quaternary International, 2025)

Stability and sensory quality of plant-based milk substitutes made from 36 different oat varieties: Relation with oat kernels attributes - Lulu Cui; Jiani Zhao; Linlin Fan; Aijinxiu Ma; Fang Zhong; Sumei Zhou; Dianzhi Hou (Journal of Cereal Science, 2025)

An AIE-TICT fluorescence probe cascade responsive to H2S, polarity and viscosity to track microenvironment changes in cellular model of ischemia-reperfusion injury - Liguo Ji; Aoxiang Fu; Yuying Zhang; Ying Xu; Yanbei Xi; Shaoli Cui; Na Gao; Linlin Yang; Wanbing Shang; Zhijun Yang; Guangjie He (Analytica Chimica Acta, 2025)

Study on strengthened the Cd(II) adsorption based on co-culture of fungi and cyanobacteria - Linlin Cui; Junjun Wang; Xueling Wu; Jiaokun Li; Weimin Zeng; Guanzhou Qiu; Li Shen (Algal Research, 2025)

NIR spectroscopy for quality assessment and shelf-life prediction of kiwifruit - Hongbo Li; Linlin Zhu; Na Li; Zhenbin Liu; Liheng Wang; Bimal Chitrakar; Dan Xu; Zhenkun Cui; Yanhua Tang; Liangbin Hu; Haizhen Mo (Postharvest Biology and Technology, 2024)

Total water level prediction at continental scale: Coastal ocean - Linlin Cui; Fei Ye; Y. Joseph Zhang; Haocheng Yu; Zhengui Wang; Saeed Moghimi; Gregory Seroka; Jack Riley; Shachak Pe'eri; Soroosh Mani; Edward Myers; Kyungmin Park; et al. (Ocean Modelling, 2024)

Roles of mTOR-p70S6K signaling pathway and HO-1 in ethylbenzene-induced hepatoxic effects in L02 cells - Siyu Liu; Linlin Chen; Hui Peng; Qiang Zhang; Qiang Zeng; Bo Cui; Ming Zhang (Food and Chemical Toxicology, 2024)

LncRNA018392 promotes the proliferation of Liaoning cashmere goat skin fibroblasts by upregulating CSF1R through binding to SPI1 - Mei Jin; Weiyu Fan; Suhe Lv; Tianwei Xue; Linlin Cong; Xinyang Liu; Lixin Cui (Molecular Biology Reports, 2024)

Migration of depleted uranium from a corroded penetrator in soil vadose zone in Bosnia and Herzegovina - Cui Li; Yanru Liang; Yin Ye; Fan Chen; Markus Astner; David J. Paterson; Yanlong Chen; Linlin Wang; Paul Guagliardo; Matvei Aleshin; Mario Burger; Peter M. Kopittke; et al. (Journal of Hazardous Materials, 2024)

Insights of using microbial material in fluoride removal from wastewater: A review - Linlin Cui; Junjun Wang; Hao Zhou; Shiyu Shao; Jue Kang; Xinyi Yu; Hongbo Zhao; Li Shen (Journal of Environmental Management, 2024)

Effect of silicon on the distribution and speciation of uranium in sunflower (Helianthus annuus) - Linlin Wang; Yanru Liang; Song Liu; Fan Chen; Yin Ye; Yanlong Chen; Jingjing Wang; David J. Paterson; Peter M. Kopittke; Yuheng Wang; Cui Li (Journal of Hazardous Materials, 2024)

3D-printed devices for continuous-flow lithium recovery of brines - Jiangtao Yu; Jie Zhu; Zhuo Han; Peng Cui; Haiying Mi; Anan Zhang; Linlin Chen; Xiaowei Li; Peiwen Wu; Yanhong Chao; Wenshuai Zhu; Zhichang Liu (Desalination, 2024)

The recent high occurrence of spring atmospheric droughts over central Hengduan Mountains is unprecedented in 669-year tree-ring records - Linlin Cui; Jinjian Li; Wenling An; Ningsheng Qin; Huiming Song; Yu Liu (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Correction to: Induction of forkhead box M1 (FoxM1) by EGF through ERK signaling pathway promotes trophoblast cell invasion - Yunpeng Xie; Dan Cui; Linlin Sui; Yuefei Xu; Ningning Zhang; Yanni Ma; Yinghua Li; Ying Kong (Cell and Tissue Research, 2024)

Photosynthetic microalgae microbial fuel cells for bioelectricity generation and microalgae lipid recovery using Gd-Co@N-CSs/NF as cathode - Linlin Qin; Yiming Qin; Na Cui; Xu Han; Haoran Lu; Tong Yang; Wenyan Liang (Chemical Engineering Journal, 2024)

Adsorption-desorption of 241Am(Ⅲ) on montmorillonite colloids and quartz sand: Effects of pH, ionic strength, colloid concentration and grain size - Linlin Zhang; Ling Li; Ke Chen; Qiulan Zhang; Jingli Shao; Yali Cui; Jun Zhu; Aiming Zhang; Song Yang (Journal of Environmental Radioactivity, 2024)

Bioaerosols in deodorization covers of wastewater treatment plants: Emission characteristics and health risks - Shan Zhao; Yang Liu; Jiang Chang; Jiawei Wang; Hao Peng; Baocong Cui; Jin Bai; Yanjie Wang; Linlin Hua (Chemosphere, 2024)

Tissue-specific distribution and bioaccumulation of perfluoroalkyl acids, isomers, alternatives, and precursors in citrus trees of contaminated fields: Implication for risk assessment - Zhaoyang Liu; Shun Liu; Feng Xiao; Andrew J. Sweetman; Qianqian Cui; Hao Guo; Jiayi Xu; Ziyao Luo; Mingxia Wang; Linlin Zhong; Jay Gan; Wenfeng Tan (Journal of Hazardous Materials, 2024)

Long-Term Effects of Ecological Restoration Projects on Ecosystem Services and Their Spatial Interactions: A Case Study of Hainan Tropical Forest Park in China - Jiahui Zhong; Linlin Cui; Zhiyin Deng; Yong Zhang; Jie Lin; Geng Guo; Xiang Zhang (Environmental Management, 2024)

Assessing the impact of marketization on energy poverty - Xinjie Shi; Pei Zeng; Liu Cui; Xuwen Gao; Tongwei Qiu; Qiang Jiang; Linlin Fu (Environment, Development and Sustainability, 2023)

Centennial-scale monsoon collapses during Marine Isotope Stage (MIS)7e detected in a northern Chinese stalagmite record - Wuhui Duan; Ming Tan; Lisheng Wang; Xuefeng Wang; Zhibang Ma; Linlin Cui; Zhengyi Xiao (Science China Earth Sciences, 2023)

A quantitative analysis of the impact of reclamation on the stability of coastal wetlands - Yanhui Chen; Linlin Cui; Guosheng Li; Jiping Liu; Lijuan Li; Dandan Zhao (Ocean & Coastal Management, 2023)

Evaluation and analysis of green efficiency of China's coastal ports under the "double carbon" goal: two improved DEA models with CO2 emissions - Linlin Cui; Long Chen; Xiao Yang (Environment, Development and Sustainability, 2023)

A parallel Python-based tool for meshing watershed rivers at continental scale - Fei Ye; Linlin Cui; Yinglong Zhang; Zhengui Wang; Saeed Moghimi; Edward Myers; Greg Seroka; Alan Zundel; Soroosh Mani; John G.W. Kelley (Environmental Modelling & Software, 2023)

3D-printed titanium-based ionic sieve monolithic adsorbent for selective lithium recovery from salt lakes - Jiangtao Yu; Jie Zhu; Guiling Luo; Linlin Chen; Xiaowei Li; Peng Cui; Peiwen Wu; Yanhong Chao; Wenshuai Zhu; Zhichang Liu (Desalination, 2023)

The effect of SARS-CoV-2 infection on human embryo early development: a multicenter prospective cohort study - Xiaolei Chen; Huangcong Shi; Cheng Li; Wanxia Zhong; Linlin Cui; Wenjun Zhang; Ling Geng; Kuona Hu; Mei Fang; Daimin Wei; Junhao Yan; Yun Sun; et al. (Science China Life Sciences, 2023)

Atomic-level chemical reaction promoting external quantum efficiency of organic photomultiplication photodetector exceeding 108% for weak-light detection - Linlin Shi; Yizhi Zhu; Guohui Li; Ting Ji; Wenyan Wang; Ye Zhang; Yukun Wu; Yuying Hao; Kaiying Wang; Jun Yuan; Yingping Zou; Beng S. Ong; et al. (Science Bulletin, 2023)

Development of SSR markers on the basis of the Panax notoginseng transcriptome for agronomic and biochemical trait association analyses - Linlin Su; Yingpeng Zhang; Ye Yang; Yuan Qu; Xiuming Cui; Feng Ge; Diqiu Liu (Journal of Applied Research on Medicinal and Aromatic Plants, 2023)

Global, regional, and national deaths, disability-adjusted life years, years lived with disability, and years of life lost for the global disease burden attributable to second-hand smoke, 1990–2019: A systematic analysis for the Global Burden of Disease Study - Chunxia Zhai; Dingtao Hu; Guanghui Yu; Wanqin Hu; Qiqun Zong; Ziye Yan; Yuhua Wang; Linlin Wang; Tingyu Zhang; Hongyu Sun; Ling Cai; Liangyu Cui; et al. (Science of The Total Environment, 2023)

Bioimmobilization and transformation of chromium and cadmium in the fungi-microalgae symbiotic system - Junjun Wang; Qinghua Tian; Linlin Cui; Jinju Cheng; Hao Zhou; Yejuan Zhang; Anan Peng; Li Shen (Journal of Hazardous Materials, 2023)

Air pollution exposure and ovarian reserve impairment in Shandong province, China: The effects of particulate matter size and exposure window - Lihong Pang; Wenhao Yu; Jiale Lv; Yunde Dou; Han Zhao; Shanshan Li; Yuming Guo; Gongbo Chen; Linlin Cui; Jingmei Hu; Yueran Zhao; Qi Zhao; et al. (Environmental Research, 2023)

Lanthanum-modified polydopamine loaded Acinetobacter lwoffii DNS32 for phosphate and atrazine removal: Insights into co-adsorption and biodegradation mechanisms - Siyue Han; Yue Tao; Yunhe Cui; Jiaming Xu; Hanxun Ju; Linlin Fan; Lin Zhang; Ying Zhang (Bioresource Technology, 2023)

A July-August relative humidity record in North China since 1765 AD reconstructed from tree-ring cellulose δ18O - Linlin Cui; Yu Liu; Qiang Li; Huiming Song; Congxi Fang (International Journal of Biometeorology, 2021)

Formation of Oil-Particle-Aggregates: Numerical Model Formulation and Calibration - Linlin Cui; Courtney K. Harris; Danielle R. N. Tarpley (Frontiers in Marine Science, 2021)
When oil spills occur in turbid waters, the oil droplets and mineral grains can combine to form oil-particle aggregates (OPAs). The formation of OPAs impacts the vertical transport of both the oil and the mineral grains; especially increasing deposition of oil to the seabed. Though the coastal oceans can be very turbid, to date, few numerical ocean models have accounted for aggregation processes that form OPAs. However, interactions between oil and mineral aggregates may be represented using techniques developed to account for sediment aggregation. As part of Consortium for Simulation of Oil Microbial Interactions in the Ocean (CSOMIO), we modified an existing, population dynamics-based sediment flocculation model to develop OPAMOD, a module that accounts for the formation of OPAs. A zero-dimensional model using OPAMOD is shown to be capable of reproducing the size distribution of aggregates from existing laboratory experimental results. Also using the zero-dimensional model, sensitivity tests were performed on two model parameters, the fractal dimension and collision efficiency. Results showed that fractal dimension played a role in the OPA size distribution by influencing the effective particle density, which modified the number concentration of flocs for a given mass concentration. However, the modeled particle characteristics and oil sequestration were relatively insensitive to collision efficiency. To explore OPA formation for an outer continental shelf site, two simulations were conducted using a one-dimensional (vertical) implementation of the model. One scenario had high sediment concentration near the seabed to mimic storm-induced resuspension. The other scenario represented river plume sediment delivery by having high sediment concentration in surface waters. Results showed that OPA formation was sensitive to the vertical distribution of suspended sediment, with the river plume scenario creating more OPA, and sequestering more oil within OPA than the storm resuspension scenario. OPAMOD was developed within the Coupled Ocean-Atmosphere-Wave-and-Sediment Transport (COAWST) modeling system, therefore the methods and parameterizations from this study are transferrable to a three-dimensional coupled oil-sediment-microbial model developed by CSOMIO within the COAWST framework.

Development of the CSOMIO Coupled Ocean-Oil-Sediment- Biology Model - Dmitry S. Dukhovskoy; Steven L. Morey; Eric P. Chassignet; Xu Chen; Victoria J. Coles; Linlin Cui; Courtney K. Harris; Robert Hetland; Tian-Jian Hsu; Andrew J. Manning; Michael Stukel; Kristen Thyng; et al. (Frontiers in Marine Science, 2021)
The fate and dispersal of oil in the ocean is dependent upon ocean dynamics, as well as transformations resulting from the interaction with the microbial community and suspended particles. These interaction processes are parameterized in many models limiting their ability to accurately simulate the fate and dispersal of oil for subsurface oil spill events. This paper presents a coupled ocean-oil-biology-sediment modeling system developed by the Consortium for Simulation of Oil-Microbial Interactions in the Ocean (CSOMIO) project. A key objective of the CSOMIO project was to develop and evaluate a modeling framework for simulating oil in the marine environment, including its interaction with microbial food webs and sediments. The modeling system developed is based on the Coupled Ocean-Atmosphere-Wave-Sediment Transport model (COAWST). Central to CSOMIO’s coupled modeling system is an oil plume model coupled to the hydrodynamic model (Regional Ocean Modeling System, ROMS). The oil plume model is based on a Lagrangian approach that describes the oil plume dynamics including advection and diffusion of individual Lagrangian elements, each representing a cluster of oil droplets. The chemical composition of oil is described in terms of three classes of compounds: saturates, aromatics, and heavy oil (resins and asphaltenes). The oil plume model simulates the rise of oil droplets based on ambient ocean flow and density fields, as well as the density and size of the oil droplets. The oil model also includes surface evaporation and surface wind drift. A novel component of the CSOMIO model is two-way Lagrangian-Eulerian mapping of the oil characteristics. This mapping is necessary for implementing interactions between the ocean-oil module and the Eulerian sediment and biogeochemical modules. The sediment module is a modification of the Community Sediment Transport Modeling System. The module simulates formation of oil-particle aggregates in the water column. The biogeochemical module simulates microbial communities adapted to the local environment and to elevated concentrations of oil components in the water column. The sediment and biogeochemical modules both reduce water column oil components. This paper provides an overview of the CSOMIO coupled modeling system components and demonstrates the capabilities of the modeling system in the test experiments.

Spatiotemporal evolution of C3/C4 vegetation and its controlling factors in southern China since the last glacial maximum - Linlin Cui; Jianfang Hu; Xu Wang (Science China Earth Sciences, 2019)

Sodium Fluoride (NaF) Induces Inflammatory Responses Via Activating MAPKs/NF-κB Signaling Pathway and Reducing Anti-inflammatory Cytokine Expression in the Mouse Liver - Linlin Chen; Ping Kuang; Huan Liu; Qin Wei; Hengmin Cui; Jing Fang; Zhicai Zuo; Junliang Deng; Yinglun Li; Xun Wang; Ling Zhao (Biological Trace Element Research, 2019)

Xylitol Production by Candida tropicalis 31949 from Sugarcane Bagasse Hydrolysate - Linlin Xu; Lei Liu; Sijia Li; Wenjing Zheng; Yuanyuan Cui; Rong Liu; Weidong Sun (Sugar Tech, 2019)

MiR-449a-5p mediates mitochondrial dysfunction and phenotypic transition by targeting Myc in pulmonary arterial smooth muscle cells - Chen Zhang; Cui Ma; Lixin Zhang; Linlin Zhang; Fengying Zhang; Mingfei Ma; Xiaodong Zheng; Min Mao; Tingting Shen; Daling Zhu (Journal of Molecular Medicine, 2019)

Relative trajectory-driven virtual dynamic occlusal adjustment for dental restorations - Sukun Tian; Ning Dai; Xiaosheng Cheng; Linlin Li; Yuchun Sun; Haihua Cui (Medical & Biological Engineering & Computing, 2019)

Lateral Circulation in a Partially Stratified Tidal Inlet - Linlin Cui; Haosheng Huang; Chunyan Li; Dubravko Justic (Journal of Marine Science and Engineering, 2018)
Using a three-dimensional, hydrostatic, primitive-equation ocean model, this study investigates the dynamics of lateral circulation in a partially stratified tidal inlet, the Barataria Pass in the Gulf of Mexico, over a 25.6 h diurnal tidal cycle. Model performance is assessed against observational data. During flood tide, the lateral circulation exhibits the characteristics similar to those induced by differential advection, i.e., lateral flow consists of two counter-rotating cells and is convergent at the surface. The analysis of momentum balance indicates that, in addition to the pressure gradient and vertical stress divergence, nonlinear advection and horizontal stress divergence are also important contributors. During ebb phase, the lateral circulation is mostly toward the right shoal (when looking into the estuary) for the whole water column and persisting for almost the whole period. The surface divergence suggested by the differential advection mechanism lasts for a very short period, if it ever exists. The main momentum balance across most of the transect during ebb is between the along-channel advection of cross-channel momentum and pressure gradient. The sectional averaged lateral velocity magnitude during ebb is comparable to that during flood, which is different from the idealized numerical experiment result.

Analyzing Coastal Wetland Degradation and its Key Restoration Technologies in the Coastal Area of Jiangsu, China - Linlin Cui; Guosheng Li; Ninglei Ouyang; Fengyun Mu; Fu Yan; Youtian Zhang; Xiaoyang Huang (Wetlands, 2018)

Fermentation Kinetics of Enzymatic Hydrolysis Bagasse Solutions for Producing l-Lactic Acid - Yuanyuan Cui; Rong Liu; Linlin Xu; Wenjing Zheng; Weidong Sun (Sugar Tech, 2018)

Main Features and Problems of Modern Evolution Process of Coastal Wetlands in North Jiangsu, China - Ninglei Ouyang; Guosheng Li; Linlin Cui; Huajun Liao (Journal of the Indian Society of Remote Sensing, 2018)

Co-Delivery of Doxorubicin and Survivin shRNA-Expressing Plasmid Via Microenvironment-Responsive Dendritic Mesoporous Silica Nanoparticles for Synergistic Cancer Therapy - Zhengxiong Li; Linlin Zhang; Cui Tang; Chunhua Yin (Pharmaceutical Research, 2017)

MiR-125a regulates mitochondrial homeostasis through targeting mitofusin 1 to control hypoxic pulmonary vascular remodeling - Cui Ma; Chen Zhang; Mingfei Ma; Lixin Zhang; Linlin Zhang; Fengying Zhang; Yingli Chen; Fangyuan Cao; Minghui Li; Guangtian Wang; Tingting Shen; Hongmin Yao; et al. (Journal of Molecular Medicine, 2017)

The death of the circulatory system diseases in China: provincial socioeconomic and environmental perspective - Haixia Pu; Jiatian Li; Pin Wang; Linlin Cui; Huaxin Wang (Environmental Science and Pollution Research, 2017)

CD19+ Tim-1+ B cells are decreased and negatively correlated with disease severity in Myasthenia Gravis patients - Yong Zhang; Xiuying Zhang; Yan Xia; Xiao Jia; Hao Li; Yanyan Zhang; Zhen Shao; Ning Xin; Mingfeng Guo; Jing Chen; ShuangShuang Zheng; YuZhong Wang; et al. (Immunologic Research, 2016)

Reactive oxygen species effect PASMCs apoptosis via regulation of dynamin-related protein 1 in hypoxic pulmonary hypertension - Lixin Zhang; Cui Ma; Chen Zhang; Mingfei Ma; Fengying Zhang; Linlin Zhang; Yingli Chen; Fangyuan Cao; Shuzhen Li; Daling Zhu (Histochemistry and Cell Biology, 2016)

Zircon ages and Hf isotopic compositions of Permian and Triassic A-type granites from central Inner Mongolia and their significance for late Palaeozoic and early Mesozoic evolution of the Central Asian Orogenic Belt - Yuruo Shi; J. Lawford Anderson; Linlin Li; Jing Ding; Cui Liu; Wei Zhang; Chonghui Shen (International Geology Review, 2016)

Characterization of chromophoric dissolved organic matter and relationships among PARAFAC components and water quality parameters in Heilongjiang, China - Hongyang Cui; Jianhong Shi; Linlin Qiu; Yue Zhao; Zimin Wei; Xinglei Wang; Liming Jia; Jiming Li (Environmental Science and Pollution Research, 2016)

Bioavailability of riverine dissolved organic carbon and nitrogen in the Heilongjiang watershed of northeastern China - Jianhong Shi; Hongyang Cui; Liming Jia; Linlin Qiu; Yue Zhao; Zimin Wei; Junqiu Wu; Xin Wen (Environmental Monitoring and Assessment, 2016)

Induction of forkhead box M1 (FoxM1) by EGF through ERK signaling pathway promotes trophoblast cell invasion - Yunpeng Xie; Dan Cui; Linlin Sui; Yuefei Xu; Ningning Zhang; Yanni Ma; Yinghua Li; Ying Kong (Cell and Tissue Research, 2015)

Integrated Approach Based on a Regional Habitat Succession Model to Assess Wetland Landscape Ecological Degradation - Linlin Cui; Guosheng Li; Huajun Liao; Ninglei Ouyang; Yue Zhang (Wetlands, 2015)

Generation of bi-transgenic pigs overexpressing human lactoferrin and lysozyme in milk - Dan Cui; Jia Li; Linlin Zhang; Shen Liu; Xiao Wen; Qiuyan Li; Yaofeng Zhao; Xiaoxiang Hu; Ran Zhang; Ning Li (Transgenic Research, 2015)

Modified Nonparametric Weighted Feature Extraction Algorithm - Linlin Cui; Guosheng Li; Huiru Ren; Lei He; Huajun Liao (Journal of the Indian Society of Remote Sensing, 2015)

Multi-scale variability of water discharge and sediment load into the Bohai Sea from 1950 to 2011 - Huiru Ren; Guosheng Li; Linlin Cui; Lei He (Journal of Geographical Sciences, 2015)

Study on Evolution Features and Spatial Distribution Patterns of Coastal Wetlands in North Jiangsu Province, China - Huajun Liao; Guosheng Li; Linlin Cui; Ninglei Ouyang; Yue Zhang; Shaohua Wang (Wetlands, 2014)

Mesoaccumbens dopamine signaling alteration underlies behavioral transition from tolerance to sensitization to morphine rewarding properties during morphine withdrawal - Linlin Sun; Ling Hu; Yijing Li; Cailian Cui (Brain Structure and Function, 2014)

Identification of Novel MicroRNA Signatures Linked to Experimental Autoimmune Myasthenia Gravis Pathogenesis: Down-Regulated miR-145 Promotes Pathogenetic Th17 Cell Response - Jiao Wang; Shuangshuang Zheng; Ning Xin; Changxin Dou; Linlin Fu; Xiuying Zhang; Jing Chen; Yanyan Zhang; Deqin Geng; Chenghua Xiao; Guiyun Cui; Xia Shen; et al. (Journal of Neuroimmune Pharmacology, 2013)

Transcriptome profiling of the developing postnatal mouse testis using next-generation sequencing - Wei Gong; LinLin Pan; Qiang Lin; YuanYuan Zhou; ChengQi Xin; XiaoMin Yu; Peng Cui; SongNian Hu; Jun Yu (Science China Life Sciences, 2013)

Expression of hGM-CSF in silk glands of transgenic silkworms using gene targeting vector - Renyu Xue; Huimei Chen; Linlin Cui; Guangli Cao; Wenlin Zhou; Xiaojian Zheng; Chengliang Gong (Transgenic Research, 2012)

Application of ATOVS radiance-bias correction to typhoon track prediction with Ensemble Kalman Filter data assimilation - Limei Cui; Jianhua Sun; Linlin Qi; Ting Lei (Advances in Atmospheric Sciences, 2011)